Pengaruh sosial media marketing activities terhadap customer response pada Chatime - Fatmawati, Tri Indah; Zuliestiana, Dinda Amanda (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Currently technology continues to progress where the impact given is very large, especially in the business world. Sosial media Instagram is one of the platforms most widely used by business people in conducting marketing activities or commonly called Sosial Media Marketing Activities. This study aims to determine whether the influence of sosial media marketing activities carried out by Chatime has an influence on customer response, namely e-wom and commitment which is mediated through brand equity variables. The dimensions of brand equity that will be measured are brand awareness and brand image. This study uses quantitative methods. Respondent data was collected by distributing questionnaires through sosial media and the analytical technique used was Structural Equation Modeling (SEM) with the help of SmartPLS software. The samples used are Chatime consumers, Instagram sosial media users and followers who have accessed Chatime Instagram sosial media accounts. The results showed that the hypothesis contained in the study had a positive influence between sosial media marketing activities on customer response, namely e-wom and commitment as well as brand awareness and brand image.